Agenesis of the internal carotid artery with intercavernous anastomosis. - Midkiff, R B; Boykin, M W; McFarland, D R; Bauman, J A (American Journal of Neuroradiology, 1995)
We report a case of unilateral agenesis of the internal carotid artery with intercavernous anastomosis, a rare development anomaly. MR and carotid ultrasound, in association with clinical awareness, can be used to diagnose this condition.